Description of a new species of the genus Yunnanilus Nichols, 1925 (Teleostei: Nemacheilidae) from Yunnan, China - Chen, Ziming; Yang, Jian; Yang, Junxing (Zootaxa, 2012)
A new species of the family Nemacheilidae, Yunnanilus niulanensis, is described from the upper reach of the NiulanjiangRiver, a branch of the Jinsha River, in Songming County, Yunnan Province, China. It can be distinguished from all otherYunnanilus species by the combination of the following characters: dorsal fin rays iii, 9; anal fin rays iii, 5; pectoral finrays i, 11; pelvic fin rays i, 7–8; branched caudal fin rays 14; mouth subterminal; 9–11 gillrakers on the inner side of thefirst gill arch, no gillrakers on the outer side; upper two-thirds of body and head covered by large brown spots; fins hyaline;body covered with scales; no lateral line; no cephalic sensory pores; caudal-peduncle length less than caudal-peduncledepth; caudal-peduncle length 9.2–11.1 % SL; body depth 21.0–25.8 % SL; eye diameter 5.4–6.0 % SL; interorbital width 9.9–12.1 % SL.